GeneXpert MTB/RIF and Mycobacterium tuberculosis Sputum Culture in Establishing the Diagnosis of Pulmonary Tuberculosis and Rifampicin Resistance in Suspected Childhood Pulmonary Tuberculosis in Soetomo Hospital - Rarome, Berlian Beatrix; Aisah, Nurul; Setyoningrum, Retno Asih; Mertaniasih, Ni Made (Institute of Topical Disease Universitas Airlangga, 2020)
The diagnosis of childhood tuberculosis remains a challenge worldwide. The GeneXpert MTB/RIF test, a rapid Mycobacteria tuberculosis diagnostic tool, was recommended for use in children. No pediatric studies of GeneXpert MTB/RIF assessing pulmonary tuberculosis within a hospital setting has been done in Indonesia. We evaluated the performance of the GeneXpert MTB/RIF test compared with sputum culture on Lowenstein-Jensen (LJ) for the diagnosis of childhood pulmonary tuberculosis. This study was conducted in pediatric respirology inpatient and outpatient Dr. Soetomo Hospital, a tertiary care facility in Surabaya between June and August 2015 with a cross-sectional design. We consecutively enrolled 27 children aged 3 months to 14 years who had history of close contact with adult tuberculosis patients and showed symptoms of pulmonary tuberculosis. Sputum collection was performed by induced sputum and three examination methods were performed (microscopic, GeneXpert MTB/RIF and sputum culture) simultaneously followed by a drug sensitivity test for specimens detected with MTB growth. The GeneXpert MTB/RIF test had a sensitivity of 100% (95% CI 100-100) and a specificity of 95% (95% CI 85-100). The positive predictive value for diagnosing pulmonary TB was 89% (95% CI 68-100), the negative predictive value was 100% (95% CI 100-100) and positive likelihood ratio was 20 (95% CI 2.82-128). The GeneXpert MTB/RIF test on one sputum sample rapidly and correctly identified all children with culture-confirmed pulmonary tuberculosis with high specificity. Similar results were obtained between GeneXpert MTB/RIF and sputum culture based on age groups and clinical manifestations. Rifampicin resistance were both detected in GeneXpert MTB/RIF and MTB sensitivity test